The impact of sensory marketing on customer satisfaction: A field study on restaurants visitors in Damascus city (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This research aimed to analyze the relationship between sensory marketing comprising five dimensions: (visual, auditory, olfactory, gustatory, and tactile marketing) and customer satisfaction within the restaurant sector in Damascus. Additionally, it examines significant differences in participants' perceptions of this relationship based on the gender variable. The research adopted a descriptive methodology, targeting restaurant-goers in Damascus as the research population. Due to the difficulty of defining the entire population and the lack of a comprehensive sampling frame, data were collected from a sample of 405 accessible restaurant visitors at various locations and times using a questionnaire designed based on previous literature. Data were analyzed using SPSS V.25 and AMOS V.25 to verify scale reliability and test the structural model hypotheses. Results revealed a statistically significant positive effect of sensory marketing on customer satisfaction. Olfactory, visual, and auditory dimensions emerged as most influential, while no significant effect was found for gustatory and tactile marketing. Findings also indicated significant gender-based differences in sensory marketing perception, favoring females, whereas no significant differences were found regarding the final satisfaction levels.
Keywords: Sensory Marketing, Customer Satisfaction, Customer Experience, Customer Behavior, Damascus Restaurants.